2019
DOI: 10.1080/20013078.2019.1599680
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐secreted extracellular vesicles promote the activation of cancer‐associated fibroblasts via the transfer of microRNA‐125b

Abstract: Tumour cells release large quantities of extracellular vesicles (EVs) to mediate their interactions with other cells in the tumour microenvironment. To identify host cells that naturally take up EVs from tumour cells, we created breast cancer cell lines secreting fluorescent EVs. These fluorescent EVs are taken up most robustly by fibroblasts within the tumour microenvironment. RNA sequencing indicated that miR-125b is one of the most abundant microRNAs secreted by mouse triple-negative breast cancer 4T1 and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 48 publications
7
91
1
Order By: Relevance
“…MicroRNAs or miRNAs are small noncoding RNA molecules that play an important role in the regulation of gene expression at the post-transcriptional level [113]. MicroRNAs have been identified across plants, animals, and viruses and within a number of human body fluids such as blood, breast milk, urine, and saliva [114][115][116][117][118][119][120][121]. These molecules can be secreted into extracellular fluid where they can be packaged into exosomes, which are membrane vesicles which contain various microRNAs [122][123][124].…”
Section: Micrornamentioning
confidence: 99%
“…MicroRNAs or miRNAs are small noncoding RNA molecules that play an important role in the regulation of gene expression at the post-transcriptional level [113]. MicroRNAs have been identified across plants, animals, and viruses and within a number of human body fluids such as blood, breast milk, urine, and saliva [114][115][116][117][118][119][120][121]. These molecules can be secreted into extracellular fluid where they can be packaged into exosomes, which are membrane vesicles which contain various microRNAs [122][123][124].…”
Section: Micrornamentioning
confidence: 99%
“…MiRNAs are among the most abundant cargo found in EVs; as such, it is unsurprising that EV-mediated miRNA transfer from cancer to stromal cells plays an important role in promoting CAF differentiation. To date, at least two dozen miRNAs have been found to be responsible for promoting EV-mediated CAF differentiation in a variety of cancer types [11,95,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116]. Uptake of miRNA-containing EVs into recipient cells results in altered expression of key signaling pathways, many of which have a known oncogenic or tumor-suppressive role, which leads to the adoption of a CAF phenotype.…”
Section: Mirnamentioning
confidence: 99%
“…In fact, the effects induced by EVs are related to modulation of the immune response. Furthermore, it has been demonstrated that EVs of tumor cells are capable of promoting immune escape by determining regulatory T cell expansion [ 159 ] and by shedding FAS ligand (FASL), as well as by inducing CD8 + T cell apoptosis and increasing expression of the MMP9 gene in melanoma cells [ 79 , 160 ].…”
Section: Pathological Roles Of Evsmentioning
confidence: 99%